KEMAMPUAN BERPIKIR KREATIF SISWA DALAM MENYELESAIKAN MASALAH KONTEKSTUAL SISTEM PERSAMAAN LINEAR DUA VARIABEL BERBANTUAN GEOGEBRA - Hilaria Yesieka Ayu Wulandari (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2024)
The purpose of this study is to describe students' ability to think creatively when facing SPLDV problems in certain contexts using the help of Geogebra. This research is qualitative research that uses the case study method to deeply understand students' creative thinking abilities. Two grade VIII junior high school students with varying initial ability levels of SPLDV were the subjects of this study. The instruments used include the SPLDV initial ability test, creative thinking ability test using Geogebra, and interview guidelines. The creative thinking test consists of four question points that measure indicators of fluency, flexibility, and novelty, with a completion time of 45 minutes. The results showed that students with high abilities could achieve the creative category (TKBK 3) because they were able to meet all indicators of fluency and novelty. Students can provide various alternative answers and use various logical strategies in solving problems. On the other hand, students with low abilities tend to fall into the less creative category (TKBK 1) because they can only meet the fluency indicator. Although subjects can provide a variety of alternative answers that are appropriate, they have not been able to describe the use of diverse strategies in solving problems.